TO THE FAUNA OF TICKS OF THE REPUBLIC OF DAGHESTAN - Zaydin M. Dzhambulatov; Magomed M. Akhmedov; Omar P. Sakidibirov (Юг России: экология, развитие)
Aim. The human factor has a significant influence on the development cycles of flora and fauna in the republic, including ticks, in which life cycles are associated with parasitization of agricultural animals, where biotopes are farm buildings, virgin and fallow pastures. Global changes in agriculture over the past two decades have led to an increase in natural pastures, reduction in the areas of sowing grasses, an increase in biotope areas and a number of parasitic ticks on animals. In this regard, we set a goal to study the ecological and biological features of the distribution of biotopes of arthropod parasites in the republic. Material and methods. The material of the study was ticks collected from cattle, sheep and horses in various zones. Collection of ticks was carried out by epizootic and regular methods. Observations, using the direct collection method, have been carried out for 7 years. Results. The researches revealed the presence of 4 genera of Ixodes ticks in the Republic: Hyalomma, Boophilus, Rhipicephalus and Dermacentor, and the genus Hyalomma occurs mainly in the Tersko-Sulak lowland, the rest can be discovered throughout the territory of Chechnya. Their species composition is represented by H. scupense, H. anatolicum, H. marginatum, H. plumbeum; B. annulatus; D. reticulatus, D. marginatus, D. daghestanicus and R. bursa. Conclusion. Through the infected eggs of the tick, further infection of the larvae takes place, which in turn, after molting, turn into the nymph and infect healthy animals, as well as the adult. The natural and climatic conditions of the Republic favor such a cycle of development of ticks.